2017
DOI: 10.30827/profesorado.v21i1.10358
|View full text |Cite
|
Sign up to set email alerts
|

Post-Bologna Policies for Teacher Education in Portugal: Tensions in Building Professional Identities

Abstract: Abstract:The article analyses the model of initial basic education teacher training in Portugal resulting from the commitments made in the framework of the Bologna Process. This analysis focuses on the impact that the policy guidelines - that point to an improvement in education quality - have on the socialization with the teaching profession. The empirical study analyses policy guidelines for teacher training and the opinions of teachers responsible for initial teacher training courses obtained through a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
2
0
6
Order By: Relevance
“…Nonetheless, the study showed that, in addition to the professors' recognition of the importance of teaching with research, several difficulties in achieving it in initial teacher education were also mentioned. Of these difficulties, those that influence the low status attributed to teaching cannot be ignored, especially when the desire is to favor teaching-research nexus strategies, in line with the European Academic perspectives of the teaching-research nexus in initial teacher education in Portugal policy that instituted the Bologna Process (Leite, 2019;Leite, Fernandes & Pereira, 2017;Robertson, 2009;Veiga & Neave, 2015). On the other hand, for this debate, it is also important to consider bureaucratic administrative procedures (Haukland, 2017), which in many universities have led to research processes mainly guided by performance evaluation goals (Martin, 2017) and not focused on didactic research.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the study showed that, in addition to the professors' recognition of the importance of teaching with research, several difficulties in achieving it in initial teacher education were also mentioned. Of these difficulties, those that influence the low status attributed to teaching cannot be ignored, especially when the desire is to favor teaching-research nexus strategies, in line with the European Academic perspectives of the teaching-research nexus in initial teacher education in Portugal policy that instituted the Bologna Process (Leite, 2019;Leite, Fernandes & Pereira, 2017;Robertson, 2009;Veiga & Neave, 2015). On the other hand, for this debate, it is also important to consider bureaucratic administrative procedures (Haukland, 2017), which in many universities have led to research processes mainly guided by performance evaluation goals (Martin, 2017) and not focused on didactic research.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the countries also differ in their teacher training programs. In Germany and Austria, an additional practical phase is added to the university studies, whereas Portugal renounces the practical phase (Leite et al, 2017). According to SEN, in Austria, as well as in Germany special schools for students with SEN still exist-however, an increasing number of students with SEN have been educated in mainstream education the last years.…”
Section: Three Countries One Educational Crisismentioning
confidence: 99%
“…Além disso, principalmente no caso da formação de professores para lecionar do 7.º ao 12.º ano de escolaridade, fica comprometido um contacto progressivo e amplo com as situações profissionais que o exercício da docência exige. Como foi defendido por Cellard et al (2021), Grossman et al (2009), Leite et al (2017); Nóvoa (2009);Rivas Flores et al (2015), a formação de professores deve oferecer condições de contacto com situações profissionais reais.…”
Section: Estrutura Curricular Dos Cursos De Formação Inicial De Profe...unclassified
“…Em síntese, e respondendo à pergunta de investigação, o modelo de formação decorrente do Processo de Bolonha, ao ser organizado numa lógica sequencial, dificulta a concretização de uma formação integrada e um contato gradual com as situações profissionais relacionadas com a docência. Por outro lado, ao ter um número de ECTS relativamente baixo para as disciplinas de IPP/PES, compromete uma socialização com a profissão que prepare para a complexidade das situações docentes do dia a dia escolar (Boyd, 2010;Freire, 2008;Imbernón, 2011;Korthagen, 2010;Leite, 2014;Leite et al, 2017;Lunenberg et al, 2007;Marcelo, 2009;Marshall, 2013;Nóvoa, 2009). Quanto à segunda pergunta de investigação, Que perfil académico e de desenvolvimento profissional têm os professores formadores que asseguram a socialização com a profissão?, os dados obtidos pelo estudo são particularmente relevantes para se refletir sobre as condições existentes para assegurar uma adequada formação inicial.…”
Section: Considerações Finaisunclassified